Effective taxation of top incomes in Germany, 1992-2002 - Stefan Bach; Giacomo Corneo; Viktor Steiner (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We analyze the taxation of top personal incomes in Germany on the basis of an integrated data file of individual tax returns and a general household survey for the years 1992 - 2002. The unique feature of this integrated data set is that it includes all taxpayers in the top percentile of the gross income distribution. We show that despite substantial tax base erosion and significant reductions of top statutory marginal tax rates, German income taxation has remained effectively progressive. The distribution of the tax burden is highly concentrated, and the effective average income tax rate of the German economic elite - the top 0.001 quantile of the gross income distribution - is about 34 percent, which is well below the legislated tax rate.
Keywords: H24; H26; D31; 330; Personal Income Tax; Taxing the Rich; Effective Progressivity; Einkommensteuer; Steuerbelastung; Reichtum; Steuerprogression; Deutschland